Comparative outcomes of two competitive devices for retrograde closure of perimembranous ventricular septal defects - Haddad, Raymond N.; Saliba, Zakhia S. (Frontiers in Cardiovascular Medicine, 2023)
Background Retrograde closure of perimembranous ventricular septal defects (pmVSDs) is a well-established procedure. However, interventionists are still looking for the best closure device. Methods We performed a single-center retrospective review of 5-year-experience (from July 2015 to July 2020) with retrograde closure of pmVSDs using AmplatzerTM Duct Occluder II (ADOII) and KONAR-MF™ VSD occluder (MFO). Deficient sub-aortic rim (SAR) (≤2.5 mm for MFO and ≤3 mm for ADOII) was an exclusion criterion in defects with a diameter ratio (right-side exit/left-side entry) > 0.5. Results We identified 77 patients (57.1% males) with a median age of 4.3 years (IQR, 2.2–8.3) and a median weight of 16 kg (IQR, 11.2–24.5). 44 (57.1%) defects (22.7% with deficient SARs) with a median left-side defect diameter of 8.7 mm (IQR, 5.7–10) were closed with ADOIIs. 33 (42.9%) defects (51.5% with deficient SARs) with a median left-side defect diameter of 10.8 mm (IQR, 8.8–13.5) were closed with MFOs. One 7/5 MFO was removed before release and upsized to a 12/10 MFO. Implantation success rate was 100% with ADOII and 90.9% with MFO devices. Two MFOs were snare-recaptured after embolization, and one 9/7 MFO was snare-retrieved for a new onset of grade-2 aortic regurgitation that persisted afterward. Median follow-up was 3.3 years (IQR, 2.1–4.2) for ADOII and 2.3 years (IQR, 1.7–2.5) for MFO. No permanent heart block or death occurred. Freedom from left ventricular dilation was 94.62% at 36 months of follow-up. Freedom from residual shunt was 90.62% for MFO and 89.61% for ADOII at 24 months of follow-up. One 2.6-year-old patient with baseline mild aortic valve prolapse and trivial aortic regurgitation developed a grade-2 aortic regurgitation after 9/7 MFO implantation. He was treated surgically after two years without device extraction. One new grade-2 asymptomatic tricuspid regurgitation persisted at the last follow-up in the ADOII group. Conclusions ADOII and MFO are complementary devices for effective retrograde closure of pmVSDs in children, including defects with absent or deficient SAR. ADOII is limited to smaller defects but offers a lower profile and a flexible left-side disk for better maneuverability over the aortic valve during retrograde implantation.